SAT0309 CARDIAC MAGNETIC RESONANCE IMAGING ELEVATED NATIVE MYOCARDIAL T1 IS PREDICTIVE FOR THE DEVELOPMENT OF MYOCARDIAL DYSFUNCTION IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Chatelus, E.; Poindron, V.; Canuet, M.; Korganow, A. S.; Germain, P.; Martin, T.; El Ghannudi, S.
Abstract : Background: All patients included in the study fulfilled the ACR/EULAR classification criteria for SSc. We prospectively included patients who underwent at least two CMR at 1.5T, including native T1 and T2 mapping (which give account for myocardial fibrosis and myocardial edema respectively), left and right ventricles morphology and functional assessment, and Late Gadolinium Enhancement (LGE) as a part of routine follow-up between 2015 and 2019. Objectives: To evaluate the prognostic value of initial abnormal T1 mapping. Methods: All patients included in the study fulfilled the ACR/EULAR classification criteria for SSc. We prospectively included patients who underwent at least two CMR at 1.5T, including native T1 and T2 mapping (which give account for myocardial fibrosis and myocardial edema respectively), left and right ventricles morphology and functional assessment, and Late Gadolinium Enhancement (LGE) as a part of routine follow-up between 2015 and 2019. Results: Sixty-three patients underwent at list two CMR during the study period. Forty-three patients were women. Mean age was 52.5±15.5 years old. Follow-up duration between the initial and the follow-up CMR was 14.5±11.5 months. Forty-one had diffuse SSc. The mean native T1 was 1066.8 ±44.6 ms. Twenty-one patients suffered from cardiac clinical manifestations. Nine patients died during the follow-up. Thirty patients (47.6%) had elevated T1 (ET1) with mean T1 1105.4±36.7 ms at the time of initial CMR. Initial ET1 was clearly correlated with: 1/ alteration of Left Ventricle (LV) Ejection fraction (EF) (r=0.5, p<0.0001) during the study period, 2/LV dilatation at initial screening and follow up (r=0.22, p=0.03 and r=0.3, p=0.02). Regarding Right ventricle, initial ET1 was correlated with initial Right Ventricle (RV) dilatation (r=0.3, p=0.02) but neither with RV volume nor RVEF at follow-up. Interestingly, initial ET1 correlated with pericardial effusion (r=0.3, p=0.003) which is known to be a pejorative prognostic factor. Seventeen patients (28%) had LGE but the ET1 at initial screening and follow-up was not correlated with LGE. Six patients had elevated T2 (ET2) which correlated with initial and follow up LV dilatation (r=0, 32, p=0.002 and r=0.5, p<0.0001 respectively) but not with LVEF during the period study. Among other parameters, initial increased BNP was correlated with follow up ET1 LVEF and RVEF (r=0.4, p=0.01; r=0.35, p=0.007; r=0, 37, p=0.005 respectively). In the same way, initial Pulmonary Arterial Hypertension (PAH) was correlated with follow up ET1 (r=0.3, p=0.02). Initial ET1 did not correlate with age, sex, cardiovascular risk factors, cardiac manifestations or death. Conclusion: Assessment of diffuse myocardial fibrosis by native T1 is predictive of the occurrence of cardiac dysfunction at the follow-up as initial ET1 was associated with decreased left ventricular function and LV and RV dilatations). These data highlights the potential role of CMR with T1mapping in initial screening and at the follow-up and provides new insights in the cardiac SSc follow up strategy. References: [1]Poindron V, Chatelus E, Canuet M, Gottenberg JE, Arnaud L, Gangi A, Gavand PE, Guffroy A, Korganow AS, Germain P, Sibilia J, El Ghannudi S, Martin T. T1 mapping cardiac magnetic resonance imaging frequently detects subclinical diffuse myocardial fibrosis in systemic sclerosis patients. Semin Arthritis Rheum. 2019 Jun 19. Disclosure of Interests: None declared